Field evaluation of a live vaccine against porcine reproductive and respiratory syndrome in fattening pigs - MAVROMATIS (Ι. ΜΑΥΡΟΜΜΑΤΗΣ) J.; KRITAS (Σ.Κ. ΚΡΗΤΑΣ) S. K.; ALEXOPOULOS (Κ. ΑΛΕΞΟΠΟΥΛΟΣ) C.; TSINAS (Α. ΤΣΙΝΑΣ) A.; KYRIAKIS (Σ.K. ΚΥΡΙΑΚΗΣ) S. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this study, a live vaccine based on an European isolate of porcine reproductive and respiratory syndrome (Porcilis PRRS, Intervet) virus has been tested in order to determine the protection of fattening pigs against the respiratory form of the syndrome under field conditions. Ten thousand pigs in an infected farm were vaccinated against PRRS virus at the age of 6 weeks and were compared to non-vaccinated pigs with respect to their health status, mortality, performance parameters (average daily gain, average daily feed intake, feed conversion ratio) and the presence of specific pathogens in their lungs. The results have shown that treated pigs became less frequently sick and have demonstrated reduced mortality compared to untreated ones. As compared to non-vaccinated animals, PRRSvaccinated pigs also performed in a better way with respect to feed conversion ratio (P<0.05) and average daily gain (P<0.05), while feed intake was similar for both groups (P>0.05). Bacteriological examinations of the lungs have revealed increased incidence of respiratory bacterial infection in untreated pigs compared to treated ones. Also a tendency for faster antibody response was detected in the vaccinées. Finally, no clinical side effects were observed after the administration of the vaccine. The results of the present study show that immunization with Porcilis PRRS (Intervet) does protect fattening pigs against the respiratory manifestations of PRRS.